Awig-Awig Sebagai Penunjang Hukum Nasional Dalam Pencegahan Alih Fungsi Lahan Di Kabupaten Buleleng - Niketut Tri Srilaksmi; Putu Ary Prasetya Ningrum; Ida Ayu Aryani Kemenuh; Komang Ayu Suseni (Tampung Penyang, 2021)
This research is based on the massive land conversion in Buleleng Regency which is indicated by the large number of shops and villas and resorts which have resulted in the reduction of productive agricultural land. Where this productive agricultural land is mostly rice fields that can support food supply in Buleleng Regency. Buleleng Regency has 9 sub-districts, 129 villages, 19 sub-districts, and 169 traditional villages. Traditional villages have an important role in maintaining these productive lands in accordance with the basic agrarian Law. So the purpose of this study is to examine the position of Awig-awig owned by traditional villages in assessing the prevention that can be done by traditional villages and the law in slowing the rate of land transfer in Buleleng Regency. In examining this problem, using a normative descriptive method, it was found that awing-awig was very important in preventing the village community from selling productive lands owned by the community.